Clinical presentation and treatment in patients with acute coronary syndrome in a tertiary care general hospital in Bangladesh - Monwar, Monalisa; Khatun, Ambia; Parvez, Masud; Naz, Tarannum; Wahed, Mir Imam Ibne; Haque, Md Ekramul; Debnath, Sumon Chandra; Khan, Md Imran (Asian Journal of Medical and Biological Research, 2018)
Acute coronary syndrome (ACS) is a leading cause of death among people in Bangladesh. The aim of the study was to analyze the clinical course and treatment strategies in patients with ACS and to determine to what extent management of ACS in a tertiary care general hospital in Bangladesh adhered to current guidelines. This study was carried out in the coronary care unit (CCU) of a tertiary care general hospital, Rajshahi, for a period of 3-months. A total number of 240 patients presenting with ACS were included in our study and the most common symptoms were acute chest pain (90%) and dyspnea (49%). The study group comprised of 27% female and 73% male patients with varying risk factors including hypertension (45%), hyperlipidemia (43%), family records of coronary artery disease (CAD) (20%), diabetes (17%) and smoking (15%). The most frequent ECG finding in patients was T wave change (71%), pathological Q wave (67%), ST segment elevation (33%), ST depression (9%), whereas, 12% patients with ACS reported to have normal ECG. Patients with ACS had elevated levels of SGOT and CK-MB. Troponin I level was positive in 100% of the patients with a mean peak troponin level of 1.5± 0.15ng/ml. In clinical setting, the patients were immediately managed with isosorbidedinitrate (58%), streptokinase (40%) and intravenous heparin (LMWH) followed by (46%) and (54%) of aspirin and aspirin-clopidogrel combinations respectively. In addition, long-term management with antihypertensive included β-blocker (58%), calcium channel blocker (29%), ACE-I (25%) and diuretics (12%). Anti-diabetic (18%) drugs were also prescribed in patients with co-existing diabetes and CAD. Adherence to guidelines is limited by lack of funds and resources in the hospital; however, attention must be paid to improve patient outcome. The average hospital stay ranges 2-3 days and hospital mortality was 10%. Asian J. Med. Biol. Res. March 2018, 4(1): 117-122